Employee Retention Analysis through Organizational Commitment and Job Satisfaction - Enjah Pipit Fitriyadi (JURNAL ECONOMINA, 2026)
This study aims to analyze employee retention through organizational commitment and job satisfaction. Employee retention has become a strategic issue for organizations because the ability to retain competent employees is closely related to cost efficiency, work continuity, knowledge preservation, and organizational competitiveness. Organizational commitment reflects employees' emotional attachment, perceived need to remain, and moral responsibility to stay with the organization, while job satisfaction reflects employees' positive evaluation of work, compensation, supervision, career opportunities, coworkers, and the work environment. This article uses a qualitative literature review method by examining theories and previous studies related to employee retention, organizational commitment, and job satisfaction. The discussion indicates that organizational commitment strengthens employee retention through affective, continuance, and normative attachment. Job satisfaction supports retention by increasing comfort, fairness perception, work motivation, and positive work experience. The integration of organizational commitment and job satisfaction can reduce turnover intention and encourage employees to remain in the organization. The study recommends that organizations develop fair compensation systems, supportive leadership, career development, employee recognition, meaningful work, and a positive work climate to improve employee retention.